Kenya : the politics of participation and control - Bienen, Henry (Princeton legacy library., 1974)
Kenya has been the object of much controversy among students of African politics. Some view it as one of the greatest "successes" of the post-independence period; others see it as an example of all that is wrong with African development. Henry Bienen approaches this controversy by asking whether the concept of political participation has been properly understood in the African context. His case study of political participation in Kenya discusses administration, party politics, ethnicity, and class. He suggests that in a system dominated by elites, individuals and groups exert influence primarily through patron-client networks and local administrative and party organs. Local politics is the most important arena for most people, it is argued. As long as the regime adopts policies which maximize economic growth and take account of peasant middle and small holders, and as long as individual representatives can be replaced even though no change of regime occurs, limited political participation leads to political stability.Originally published in 1974.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.